2020
DOI: 10.1002/rrq.362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Word‐Reading Development in English Learner University Students: A Longitudinal Eye Movement Study

Abstract: We investigated the word‐reading development of adult second‐language learners of English. A sample of 70 (Mandarin or Cantonese) Chinese‐speaking students enrolled in a university‐level English bridging program at a Canadian university silently read passages of text at the beginning and end of the program while their eye movements were recorded. At each timepoint, we also administered a battery of tests that measure key component skills of second‐language reading (phonological processing, vocabulary knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 177 publications
1
17
0
Order By: Relevance
“…The natural tendency of readers to avoid such failures also triggers a careful reading pattern, which is characterized by the absence of skipping and slower total reading times. This reading behavior might be optimal for readers who have insufficient exposure to the language (e.g., L2 learners; Gollan, Montoya, Cera, & Sandoval, 2008; Schmidtke & Moro, 2020; Whitford & Titone, 2012, 2016) or are unfamiliar with reading materials (e.g., children, adult poor readers; Barnes & Kim, 2016; Kuperman & Van Dyke, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural tendency of readers to avoid such failures also triggers a careful reading pattern, which is characterized by the absence of skipping and slower total reading times. This reading behavior might be optimal for readers who have insufficient exposure to the language (e.g., L2 learners; Gollan, Montoya, Cera, & Sandoval, 2008; Schmidtke & Moro, 2020; Whitford & Titone, 2012, 2016) or are unfamiliar with reading materials (e.g., children, adult poor readers; Barnes & Kim, 2016; Kuperman & Van Dyke, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, eye tracking has become a widely used methodology in bilingual language reading research (Cop, Dirix, Drieghe, & Duyck, 2017; Cop, Drieghe, & Duyck, 2015; Dirix, Vander Beken, De Bruyne, Brysbaert, & Duyck, 2020; Kang, 2014; Roberts & Siyanova‐Chanturia, 2013; Schmidtke & Moro, 2020; Whitford & Titone, 2012). Silent reading without metalinguistic tasks allows the study of written language comprehension in real time and, therefore, in laboratory settings, reflects the closest approach obtainable to the natural reading behavior of bilingual readers.…”
mentioning
confidence: 99%
“…Reading relates to recognize morphemes, words, and phrases to construct meaning (Nation, 2006). If learners read a text and answer reading questions or retell facts, they are assumed as good comprehender (Schmidtke & Moro, 2021). To be a good comprehender is a hope for language learners.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, researchers should endeavor to include measures of phonological awareness given its importance for the interpretation of meaning. 2 A recent study published after we conducted the current study (Schmidtke & Moro, 2020/Forthcoming) found evidence of a transition from a lexical processing strategy that is heavily reliant on phonological decoding to word-reading behavior that is more actively engaged in higher order cognitive processes, such as meaning integration. Measuring the phonological awareness should be included in the materials of future studies, including those that employ pause-insertion, as this may help to further elucidate our knowledge of the integration of prosody and syntax during auditory L2 sentence comprehension.…”
Section: Discussionmentioning
confidence: 71%